The Consequences of the Consequences: The Impact of the Environment on People With Aphasia Over Time. Issue 1 (January 2017) - O'Halloran, Robyn; Carragher, Marcella; Foster, Abby
Abstract : Understanding the impact of the environment on the participation of people with aphasia depends on one's perspective. A long-term perspective provides a unique insight into the myriad of ways in which the environment can influence the participation of people living with aphasia over decades. In this article, the authors present the real-life story of "Hank, " who has lived with aphasia for more than 15 years. The authors consider how 2 different conceptual frameworks—the International Classification of Functioning, Disability and Health and the Social Determinants of Health—account for Hank's experience. The International Classification of Functioning, Disability and Health is useful to conceptualize the range of factors that influence living with aphasia at a particular point in time. In contrast, the Social Determinants of Health is useful to conceptualize the cumulative impact of living with aphasia on long-term health and well-being. Viewing aphasia as a social condition that impacts social determinants of health has potentially wide ranging implications for service design and delivery and the role of speech–language pathologists.